(untitled) (Development Service Industry Management, 2023)
The article underscores the importance of examining the prerequisites for security-oriented development within an enterprise. The existence of these prerequisites is crucial as it determines the viability of planning and implementing the enterprise’s development within the context of preserving its economic security. These prerequisites lay the foundation for the effectiveness of this developmental process. The prerequisites for safety-oriented development within the enterprise can be categorized into two distinct parts: enterprise capabilities — this encompasses the resources and competences available to the enterprise, which can be effectively utilized in safety-oriented development. These capabilities aim to facilitate actions, processes, and operations related to planned enterprise development without compromising its economic security; threats to the enterprise safety-oriented development — these involve processes and phenomena within both the external and internal environment of the enterprise. In the presence of specific conditions within its internal environment, these threats have the potential to induce predominantly negative deviations from the planned development process. To ensure the objectivity of the results in exploring the prerequisites for security-oriented enterprise development, it is advisable to incorporate quantitative, and even quasi-quantitative (artificial), assessments of the state of these prerequisites. Fundamentally, evaluating the prerequisites for security-oriented enterprise development involves assessing the balance between the enterprise’s capabilities and the potential impact of development-related threats. In this context, modeling has been selected as a valuable tool for obtaining precise quantitative assessments of the prerequisites for security-oriented enterprise development. A quantitative assessment of the prerequisites for security-oriented enterprise development was conducted using an additive-multiplicative model. This model effectively captures the cumulative impact of both opportunities and threats, providing a comprehensive reflection that considers their respective significance. To assess each opportunity and threat within the prerequisites for security-oriented enterprise development, we have devised a conditional-quantitative ordinal (ranking) scale consisting of 5 positions. To interpret and present the results of the assessment of prerequisites for safety-oriented enterprise development in a qualitative manner, a matrix format was developed. Within each of the four quadrants of the matrix, results were interpreted, and recommendations for ensuring safety-oriented development of the enterprise were provided.